Quantum Cryptography for Future Networks Security: A Systematic Review - Durr-E-Shahwar; Muhammad Imran; Ahmed B. Altamimi; Wilayat Khan; Shariq Hussain; Mohammad Alsaffar (IEEE Access, 2024)
Quantum Cryptography (QC) revolutionizes network communication – harnessing principles of quantum mechanics to enable the exchange of encrypted messages – for enabling secure data transmission in an era of quantum information processing. With a significant rise in quantum computing research and development efforts, there is an increasing interest in exploring QC (e.g., Quantum Key Distribution (QKD) and Quantum Secured Encryption (QSE)) against a multitude of security threats in futuristic networks for quantum information processing. The objective of this study is to review the existing research i.e., consolidating the published evidence, that streamlines and documents the predominant challenges, recurring solutions, security threats, and their counter-measures against the outlined research questions in the context of QC. To conduct this study, we followed the guidelines and method of Systematic Literature Reviews (SLRs) to answer seven research questions. These questions investigate the proposed solutions for state-of-the-art QC and its impact on future network security. Based on the seven (7) outlined research questions, this study systematically selected and reviewed one hundred and thirty four (134) research studies published from 2016 to 2023 with a focus on QC for quantum information processing. The results of this SLR establish a knowledge base for modern QC applications to guarantee network security in quantum-enabled network communications. The review reveals that though still in the phase of its inception, the research on QC is progressing rapidly, highlighting the necessity for network protocol and frameworks to cater for quantum network security. The SLR also highlights the challenges encountered while designing or implementing the QC systems, pinpointing the significance of keeping abreast of QKD networks and addressing possible ramifications for internet security in the future. The SLR provides theoretical foundations and evidence-based guidelines to tackle emerging and futuristic challenges of security in the context of QC and QKD for quantum information processing.